The relationship between homeownership and food insecurity - Li, Tim (My University, 2022)
The researchers compared the odds of food insecurity between renters and homeowners with and without a mortgage, and with different home values. They also examined whether housing cost burden (ratio of housing cost to after-tax income) contributed to differences between renters and homeowners with and without a mortgage.
Keywords: Society & Community; Income, pensions, spending & wealth; Housing; Health